Pengambilkiraan Realiti Semasa Dalam Berfatwa: Analisis Terhadap Fatwa Zakat Di Selangor - Yasin, Ummi Farahin; Abdul Rahman, Noor Naemah; Mohd Shah, Mohd Faez (Jurnal Fiqh, 2017)
This article attempts to analyse and discuss the fatwa on zakat by the Selangor Mufti Department from the year 2001 to 2011. Methods used in the analysis are library research, observation and interviews. Based on the analysis, it is found that when a fatwa on zakat is issued, the current developments of the society are considered by the fatwa committee. The Fatwa on zakat is not bound to the views from any mazhabs or particular Muslim scholars.